2014
DOI: 10.1093/mnras/stu1864
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased study of debris discs around A-type stars with Herschel

Abstract: The Herschel DEBRIS (Disc Emission via a Bias-free Reconnaissance in the Infrared/Submillimetre) survey brings us a unique perspective on the study of debris discs around main-sequence A-type stars. Bias-free by design, the survey offers a remarkable data set with which to investigate the cold disc properties. The statistical analysis of the 100 and 160 µm data for 86 main-sequence A stars yields a lower than previously found debris disc rate. Considering better than 3σ excess sources, we find a detection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 63 publications
8
90
0
Order By: Relevance
“…Within the gas disk we derive an excitation temperature of T 0 = 27 -+ 4 11 K. Spitzer observations find typical dust temperatures of 50-200 K in debris disks (Morales et al 2011;Ballering et al 2013), with similar results found by Herschel (Matthews et al 2010;Eiroa et al 2013;Thureau et al 2014), although this depends strongly on the location and composition of the dust grains. In debris disks the dust temperature at a given radius is often found to be higher than that for blackbody grains, or conversely the observed radial location of the dust grains is larger than predicted for blackbody grains (Booth et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Within the gas disk we derive an excitation temperature of T 0 = 27 -+ 4 11 K. Spitzer observations find typical dust temperatures of 50-200 K in debris disks (Morales et al 2011;Ballering et al 2013), with similar results found by Herschel (Matthews et al 2010;Eiroa et al 2013;Thureau et al 2014), although this depends strongly on the location and composition of the dust grains. In debris disks the dust temperature at a given radius is often found to be higher than that for blackbody grains, or conversely the observed radial location of the dust grains is larger than predicted for blackbody grains (Booth et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…A KS test reveals no difference between single and multiple stars in terms of dust temperature (p=0.9) or LIR/L bol (p=0.5), as was also demonstrated for A stars by Thureau et al (2014). This holds regardless of whether we consider the full sample or break it as A or FGK stars: for dust temperatures we find p=0.3 for A singles vs multiples and similarly p=0.9 for FGK systems.…”
Section: Global Statisticssupporting
confidence: 67%
“…Disk systems among the sample are summarized in Matthews et al (in prep), Thureau et al (2014), and Sibthorpe et al (in prep). Despite the large number of systems considered, the number of disk-bearing systems (78 across all spectral types) is lower than considered in Rodriguez & Zuckerman (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data used 2.1. Stellar properties AU Mic (GJ 803, HD 197481) is an M1 V dwarf at a distance of 9.9 pc (Perryman et al 1997;van Leeuwen 2007). The star is a bright X-ray and UV emitter and shows strong flaring activity (e.g., Robinson et al 2001).…”
Section: Introductionmentioning
confidence: 99%